ANALISIS SISTEM AKUNTANSI PEMERINTAH PUSAT (SAPP) DI KANTOR AKUNTANSI REGIONAL JAKARTA - Wahyuni, Titis (UI Scholars Hub, 2013)
This research is intended to describe Central Government Accounting System (SAPP) implemented by the State Financial Accounting Agency (BAKUN) through The Regional Accounting Office (KAR) and the expected outcomes of Central Government Accounting System. In a accounting system, financial statements generated rely on the accuracy and validity of data input transactions. The accuracy and validity of the Government's financial statements generated will depend on the quality of the work done by KARs in managing the Government's financial transaction data input. The method usedin this research isby analyzing the problems/obstaclesfaced by KAR Jakarta and also analyzing the process performed by KAR Jakarta during 2000 – 20001. Analysis was performed on cash receipt transactiondata processingsubsystem (Cash Receipt) and governmentcashexpenditures (Cash Disbursement), and general ledger subsystem (General Ledger) used and done by using Analysis Critical Success Factor (CSF), Performance Grid, Proses Modeling, Data Modeling, and Network Modeling. The result of this research shows that there are some problems/obstacles faced by KAR in managing data of financial transactions of the Government. By using these results are then made efforts to repair the running system.